The effect of breastfeeding compared with formula milk on the growth of infants with congenital heart disease: Evidence-based case report - Melinda; Permadi, Prasetya Ismail; Yuliarto, Saptadi; Kadafi, Kurniawan Taufiq; Koentartiwi, Dyahris; Rahmadany, Aulya Farra; Fauzi, Muhammad Rizki; Muharrom, Muhammad Aji (Medical Faculty of Brawijaya University, Indonesia, 2025)
Introduction: Children with Congenital Heart Disease are at high risk of feeding and growth problems. Nutrition practices for children with CHD still vary widely across institutions, including breastfeeding. This study aims to conduct a critical review to compare the effects of breastfeeding versus formula on the growth of infants with congenital heart disease. Methods: The article search was conducted online using the PubMed, EBSCO, and ProQuest databases with the keywords “Congenital Heart Disease,” “Human Milk,” “Formula,” and “Growth.” Result: Two articles were obtained in the form of systematic review studies. Results of the study stated that in infants with CHD with breastfeeding compared to formula milk Weight for age score is better with breastfeeding because breast milk is easier to digest Conclusion. Breast milk has been shown to have significant benefits on the growth of infants with CHD compared to formula, especially in terms of weight-for-age z-score.